Legal Treatment of Extremism - KOROBEEV, Aleksandr Ivanovich; KUZNETCOV, Aleksandr Vasilyevich (Journal of Advanced Research in Law and Economics; Vol 5 No 2 (2014): JARLE Volume V, Issue 2(10), Winter 2014, 2017)
Extremism is not some kind of local phenomenon, nowadays it becomes a global threat. Going beyond national borders extremism constitutes a danger to the subjects of international relations and for international security. There are several different points of view on extremism definition. The article contains normative definition of extremism in Russia, as well as in regional agreements, and raises an issue of human rights respect in the field of struggle with extremism in the example of the USA. This article also analyzes the definitions proposed by various scientists and separate the extremism and religious fundamentalism. The purpose of the article is to reveal the essence of such category as ‘extremism’.